TEACHING THE USE OF VERBAL INFLUENCE TOOLS IN THE DEVELOPMENT OF LEXICAL COMPETENCES OF THE STUDENT AS A METHODOLOGICAL PROBLEM (Spectrum Journal of Innovation, Reforms and Development, 2024)
In this article, the mother tongue is a necessary element of the general culture of every citizen of our country today, and young people who have graduated from a general education school should be able to use the Uzbek language freely, effectively and appropriately in various aspects of social, economic and cultural life, in all types of communication and interaction, it is said that they should have the necessary knowledge, skills and abilities to fully enjoy its unlimited possibilities.